The relationship between diastolic blood pressure and the risk of cardiovascular events in patients with atrial fibrillation whose systolic blood pressure was treated to less than 130 mmHg. (14th October 2021) - Ikeda, S; Iguchi, M; Ogawa, H; Ishigami, K; Doi, K; Hamatani, Y; Ide, Y; Fujino, A; Ishii, M; Masunaga, N; Esato, M; Wada, H; et al.
Abstract: Background: Hypertension is one of the major risk factors of cardiovascular events in patients with atrial fibrillation (AF). Low diastolic blood pressure (DBP) has been reported to be associated with the incidence of cardiovascular events, but current guidelines recommend an intensive blood pressure target of less than 130/80 mmHg for AF patients taking oral anticoagulants without mentioning the lower limits of DBP. Methods: The Fushimi AF Registry is a community-based prospective survey of AF patients in a city of Japan. Follow-up data were available in 4, 472 patients, and hypertensive patients who received prescription of any antihypertensive agents and whose systolic blood pressure was treated to less than 130 mmHg were available were examined (n=1, 319). We divided the patients into four groups according to their DBP at baseline; G1 (DBP<60 mmHg, n=349), G2 (60≤DBP<70, n=434), G3 (70≤DBP<80, n=386) and G4 (80≤DBP, n=150), and compared the clinical background and outcomes among groups. Results: The proportion of female was grater in G1 group, and the patients in G1 group were older. During the median follow-up of 2, 458 days, in Kaplan-Meier analysis, the incidence rates of cardiovascular events (composite of cardiac death, ischemic stroke, systemic embolism, non-fatal myocardial infarction and heart failure hospitalization during follow up) were the highest in G1 group and the lowest in G3 group (G1: 7.2% per person-year vs. G2: 4.9% vs. G3: 2.2% vs. G4: 4.4%; p<0.01). Multivariate Cox proportional hazards regression analysis revealed that DBP was an independent determinant of cardiovascular events (G1 vs. G3; hazard ratio (HR): 1.96, 95% confidence intervals (CI): 1.39–2.76, G2 vs. G3; HR: 1.79, 95% CI: 1.28–2.50, G4 vs. G3; HR: 1.56, 95% CI: 0.99–2.45) (Figure 1). When we examined the association of DBP according to 10 mmHg increment, patients with excessively low DBP (<50 mmHg) had significantly higher incidence of cardiovascular events than patients with DBP of 70–79 mmHg (HR: 2.80, 95% CI: 1.81–4.33), and DBP exhibited J curve association with higher incidence of cardiovascular events (Figure 2). Conclusion: In Japanese AF patients whose systolic blood pressure was treated to less than 130 mmHg, patients with excessively low DBP had significantly higher incidence of cardiovascular events, and DBP exhibited J curve association with higher incidence of cardiovascular events. Funding Acknowledgement: Type of funding sources: None.